Human Papillomavirus (HPV) in oral cavity lesions: comparison with other oral cancer risk factors - Venezuela, Raul Fernando (2013)
Human papillomavirus (HPV) is considered a necessary factor for the development of cervical cancer; however, its relationship with oral cancer is controversial. The aim of this study was detect the presence of HPV in lesions of the oral cavity and its correlation with other risk factors. Presence of HPV was studied by polymerase chain reaction in samples from benign lesions, potentially malignant lesions (PML), neoplasias and healthy mucosae. The results from the different groups were compared; in addition to their histopathological variables with tobacco smoking, alcohol consumption, so on. HPV was detected in 88.89% of benign lesions, 41.38% of PML and 56.25% of neoplasias. The most prevalent genotypes were 16 and 6. Together, reached 55% of the total number of cases. A significant association was observed between HPV and male gender, tobacco smokers, alcohol drinkers and benign lesions. Tobacco smoking and alcohol intake were associated to neoplasias. Our results showed that factors like tobacco smoking and alcohol drinking, have more influence than HPV in the development of oral neoplasias; however, 56.2% of the neoplasias tested positive for HPV; the percentage of HR-HPV detection increased with the severity of the lesions, suggesting its possible involvement in malignant processes.